AN ANALYSIS OF ADJACENCY PAIRS IN SPEAKING CLASS AT CEC KAMPOENG PARE MATARAM 2022 - Purnawan Aropi; Sahuddin; Yuni Budi Lestari (Journal of English Education Forum (JEEF), 2022)
This study aimed at finding and analyzing the types of Adjacency Pairs and their preference structures used by a teacher and students in speaking class. This study used a descriptive research method using changing observer. The sample included teacher and students of 2nd Level speaking class at Cake English Course (CEC) Kampoeng Pare Mataram. The data were collected using video recording then transcribed to be analyzed. The study shows that there are eleven types of adjacency pairs and seven of their preference structures discovered in teaching learning process. The first type is question – answer in which its preference structure is expected as preferred response and unexpected as unpreferred one. The second type is request – acceptance/rejection which acceptance is as preferred and rejection as unpreferred response of its preference structure. The next type is apology – acceptance/refusal in which both preferred and unpreferred occurred as preference structures in this type. Then, complaint – apology/denial was found in which its preference structure is preferred and unpreferred. Furthermore, invitation – acceptance in which its acceptance response is known as preferred response in preference structure. Lastly, suggestion – disagreement and offer – rejection, each of this pair has its preference structure in formed of unpreferred. However, announcement – acknowledgment, greeting – greeting, summon – answer and closing – closing adjacency pairs also occurred in this study, yet their preference structure does not exist.